Ecological niche modelling and coalescent simulations to explore the recent geographical range history of five widespread bumblebee species in Europe. (20th June 2016) - Dellicour, Simon; Kastally, Chedly; Varela, Sara; Michez, Denis; Rasmont, Pierre; Mardulyn, Patrick; Lecocq, Thomas
Abstract: Aim: Studying the changes in species ranges during the last glaciation event is an important step towards the understanding of the observed patterns of intra‐specific genetic variability. We focused on bumblebees, an interesting biological model to address these questions because cold‐adapted species are likely to have experienced different geographical range histories during the last glacial period compared to more commonly studied, strictly temperate, species. We investigated and compared historical hypotheses regarding the geographical range of five common and co‐distributed West Palaearctic bumblebee species. Location: Europe, West Palaearctic. Methods: For each species, we inferred present and past (Last Glacial Maximum) distributions from species occurrence records, and present and past climatic data, using the ecological niche modelling (ENM) approach implemented inMaxent . Based on genetic data previously obtained from the sequencing of three gene fragments (mitochondrial locus COI and two nuclear loci EF‐1α and PEPCK ), we then compared global and local patterns of genetic variation using several summary statistics as well as a visual mapping of genetic variation. Finally, we used a spatially explicit model of DNA sequence coalescence to test and compare four evolutionary scenarios derived from ENM results and patterns of genetic diversity. Results: Ecological niche modelling results based on climatic data clearly suggested a range continuum in Europe during the last glaciation. Yet, the related evolutionary scenario involving such continuum was less supported than alternative scenarios involving a more fragmented distribution. Indeed, for the three out of five species for which genetic data allowed discriminating among tested scenarios, the scenario that included a fragmented range during the last glaciation was identified as the most likely. Main conclusions: Although ENM suggested that bumblebees would have maintained a range continuum across Europe during the last glaciation, coalescent simulations tended to refute the persistence of a large range continuum for these species during this period. This suggests that even for cold‐adapted species, the cooling periods have significantly shrunk and fragmented their respective ranges.